The Pinecone 1944 - (:unkn) unknown (Georgia State Womans College, 1944)
The presentation of the 1944 Pine Cone represents, to the best of each staff member's ability, during the confusion and strife of a war torn world, the memories cherished by each G. S. W. C. student. It has been the purpose of the Pine Cone staff to relate in words and pictures the events that have been impressed upon each student of G. S. W. C. during the record year, 1943-44. This year has brought changes, new environments, the lack of funds and commodities which we once thought essential, and all our efForts have been unselfishly concentrated on various ways in which we might best serve and help to make a better post-war world. In our hearts we have a new purpose and new determination that those who have died and those that will die in this war will not have died in vain. To you who will share such a responsibility in the various walks of life which each of you will choose and to you who will continue to share your responsibility here—we offer these pages with the hope that always they will represent cherished memories and ideals.
The Pine Cone 1944 at Valdosta, Georgia
1944 Yearbook of the Georgia State Womans College, Valdosta, Georgia
Keywords: 1944; Georgia State Womans College; Yearbook